Eldri heimildir um heyöflun og heysjúkdóma á Íslandi - Davíð Gíslason1; Einar G. Pétursson; Tryggvi Ásmundsson (Læknafélag Íslands, 2021)
To access publisher's full text version of this article, please click on the hyperlink in Additional Links field or click on the hyperlink at the top of the page marked Download Heysjúkdómar hafa vafalaust fylgt búskaparháttum Íslendinga alveg frá landnámi í lok 9. aldar. Þó hafa aðstæður til heyöflunar verið betri á fyrstu öldum eftir landnám en seinna varð, þegar veðurfar kólnaði og landgæði versnuðu. Greinin fjallar um það sem skrifað hefur verið um heysjúkdóma á Íslandi frá byrjun 17. aldar og fram á miðja 20. öldina. Diseases connected with work in hay have existed in Iceland since its settlement late in the 9th century. Haymaking was probably easier in those days because of better climate and land quality but became more difficult later when these factors deteriorated. First data on diseases connected with hay are from the early 17th century where the word „haysickness“ (in Icelandic „heysótt“) is used in a book on treatment of diseases. Later in the century the word is found in a rhyme that says „short of breath due to haysickness“. The word „haysickness“ is also found in dictionaries from that time. In a book from 1730-40 says: „Haysickness sometimes causes illness and loss of appetite in those that loosen hay in a compressed haystack with a hayneedle or a hook.“ At the end of the 18th century Jón Pétursson writes a good description of hay diseases: „It cannot be denied that haysickness not taken seriously or long ignored can cause many deaths in this country.“ Jón Finsen mentions in his doctoral thesis in 1874 that the symptoms of haysickness are different from those of allergy to pollen (hay fever) that had been recently described. In 1870 the Director of Health writes directions for farmers on how to reduce the danger of getting haysickness by using a thin cloth facemask when loosing hay from a haystack.